Agricultural use of sewage sludge in India: benefits and potential risk of heavy metals contamination and possible remediation options – a review. (2017) - Saha, Sushanta; Saha, Bhola Nath; Pati, Sajal; Pal, Biplab; Hazra, Gora Chand
Application of municipal sewage sludge in agriculture is one of the best options for its safe disposal as it provides an opportunity to recycle plant essential nutrients (N, P, secondary nutrients and micronutrients) and improves soil physical, chemical and biological properties due to high organic matter content. Yield and productivity of a wide range of crops has been improved due to soil application of sewage sludge than that of well-fertilised control. Depending upon the origin, sewage sludge often contains very high amount of potentially toxic heavy metals and as such their excessive use for a longer period increases metal bioavailability in soil and ultimately causes food chain contamination. In this article we reviewed the available information on various aspects of land application of municipal sewage sludges on crop yield, soil fertility and problems of heavy metals accumulation in edible portion of the crops as well as possible options for remediation of heavy metals toxicity in contaminated soils to explore the possibility of safe recycling this waste in agriculture.